Horizontes de interpretación en la enseñanza y aprendizaje del español y la literatura - Moreno Torres, Mónica; Carvajal Córdoba, Edwin; Buitrago Montoya, Hugo; Ospina Álvarez, Teresita; Ortiz Naranjo, Nancy (Enunciación, 2001)